Isolated Glossopharyngeal Nerve Herpes Zoster Infection Following Varicella Vaccination in an Emergency Physician: A Case Report - Mavia Najam (15954224) (2025)
Background Herpes zoster can affect the cranial nerves but rarely it involves the glossopharyngeal nerve in isolation. Varicella zoster virus (VZV) infection most often occurs in the context of previous varicella infection, but it is exceedingly rare in immunocompetent vaccinated patients without previous infection. Case Report We report a unique case of a 34-year-old immunocompetent male presenting with severe throat pain, odynophagia, and headache, accompanied by vesicles on the left side of hard and soft palate, base of the tongue, and the posterior pharyngeal wall. Notably, the patient had no history of chickenpox but had previous varicella vaccination. Polymerase chain reaction analysis (PCR) from the throat swab confirmed varicella-zoster virus infection. Antiviral therapy and aggressive pain management led to symptom resolution. However, the patient developed nausea, anorexia, intractable hiccups and cough lasting several days. Why should an emergency physician be aware of this? This case highlights the importance of considering herpes zoster in atypical cranial nerve presentations, raises questions about the pathogenesis of herpes zoster reactivation following live vaccination, and emphasizes the need for prompt recognition and treatment to prevent complications. Other Information Published in: The Journal of Emergency Medicine License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jemermed.2025.08.032